2015
DOI: 10.1038/aps.2014.150
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β suppresses the proliferation of rat hepatic oval cells through modulating Wnt/β-catenin signaling pathway

Abstract: Aim: Glycogen synthase kinase 3β (GSK-3β) plays a crucial role in hepatic biology, including liver development, regeneration, proliferation and carcinogenesis. In this study we investigated the role of GSK-3β in regulation of growth of hepatic oval cells in vitro and in liver regeneration in partially hepatectomized rats. Methods: WB-F344 cells, the rat hepatic stem-like epithelial cells, were used as representative of oval cells. Cell viability was examined using a WST-8 assay. The cells were transfected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
2
14
1
Order By: Relevance
“…Glycogen synthase kinase-3β (GSK-3β), a widespread cellular serine/threonine kinase, plays a key role in the regulation of various signaling pathways, including Wnt/β-catenin signaling [35, 36]. In the Wnt pathway, GSK-3β is found in multimeric composites composed of the adenomatous polyposis coli (APC) protein, axin and β catenin [37], where it causes phosphorylation of the N-terminal Ser/Thr in β-catenin [38]. It was revealed that the suppression of GSK-3β can activate Wnt signaling and β-catenin through dephosphorylation, where GSK-3β functions as an inhibitor of the Wnt pathway [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycogen synthase kinase-3β (GSK-3β), a widespread cellular serine/threonine kinase, plays a key role in the regulation of various signaling pathways, including Wnt/β-catenin signaling [35, 36]. In the Wnt pathway, GSK-3β is found in multimeric composites composed of the adenomatous polyposis coli (APC) protein, axin and β catenin [37], where it causes phosphorylation of the N-terminal Ser/Thr in β-catenin [38]. It was revealed that the suppression of GSK-3β can activate Wnt signaling and β-catenin through dephosphorylation, where GSK-3β functions as an inhibitor of the Wnt pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the Wnt pathway, GSK-3β is found in multimeric composites composed of the adenomatous polyposis coli (APC) protein, axin and β catenin [37], where it causes phosphorylation of the N-terminal Ser/Thr in β-catenin [38]. It was revealed that the suppression of GSK-3β can activate Wnt signaling and β-catenin through dephosphorylation, where GSK-3β functions as an inhibitor of the Wnt pathway [38]. Wnts are secreted proteins that bind to a Frizzled receptor and lipoprotein receptor-related protein 5 (LRP5) or LRP6 co-receptor, which results in an increased level of β-catenin because its degradation via the proteasome is prevented [39].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding was in accordance with the previous report that 1.4% of all hepatocytes were derived from nonhepatocytes during liver regeneration after two-thirds PH (Malato et al 2011). Unlike LSECs, progenitor cells such as oval cells and/or hepatic stellate cells have been previously reported to convert into hepatocytes during liver regeneration Ji et al 2015). Since Tie2-Cre-mediated excision could also occur in non-endothelial populations such as mesenchymal cells surrounding the vitelline artery (Li et al 2006;Lan et al 2014), mice expressing Cre recombinase under the control of the VE-Cadherin promoter (Zovein et al 2008) were used to trace the fate of endothelial cells during liver regeneration.…”
Section: Gene Primersupporting
confidence: 94%
“…; Ji et al . ). Since Tie2‐Cre‐mediated excision could also occur in non‐endothelial populations such as mesenchymal cells surrounding the vitelline artery (Li et al .…”
Section: Resultsmentioning
confidence: 97%
“…Because β-catenin is a key component of the Wnt/β-catenin pathway, enhancing its expression activates the downstream signaling pathway [38]. In our study, we found that TWS119 increased the expression of claudin-3 compared with that in the rtPA group.…”
Section: Discussionsupporting
confidence: 49%